MaxEnt-based Habitat Suitability Modeling of Tor tor (Hamilton 1822) under Climate Change Scenario in Arunachal Pradesh, India - Mahato, Ranjit; Abujam, Santoshkumar; Gautam, Bikash Jyoti; Nimasow, Oyi Dai; Barman, Bikul; Nimasow, Gibji; Das, Debangshu Narayan (International Journal of Ecology and Environmental Sciences, 2025)
The Indian Himalayan Region is home to numerous freshwater fish species, while wild stock is declining at an alarming rate due to human interventions and the impact of climate change. Arunachal Pradesh has a variety of fish habitats with a high degree of endemism. Species distribution models predict the probable species distribution under current and future climatic conditions. Hence, an attempt has been made to predict the habitat suitability of Tor tor in the drainage systems of Arunachal Pradesh (current and future). The study used the Maximum Entropy technique with seven environmental variables and 40 species occurrence records. The model performance was consistent with an area under the ROC curve of 0.97 and true skill statistics of 0.889. The species distribution was highly influenced by flow accumulation, elevation, and minimum temperature of the coldest month. The model showed a total river length of 815.62 km as very high and 814.74 km as high suitable habitat of T. tor in the mid-altitude and lower reaches of the major rivers like Kameng, Subansiri, Siang, Lohit, and Tirap under the current climate. The results of future climate (SSP245 and SSP585) showed a significant gain in the high and very high suitable categories with a shift of suitable habitat towards the northern parts. The findings could help to formulate conservation strategies for T. tor under climate change scenarios.